French activity on high temperature corrosion in water vapor - Chevalier, Sébastien; Favergeon, Jérôme (Materials science foundations, 2014)
Increased clarity in our understanding of water vapor effects on oxidation is resulting from our recognition that multiple mechanisms are possible, and that distinctions must be drawn between situations where, on the one hand, molecular oxygen accompanies water vapor, and on the other, it does not, and instead free hydrogen can be present. It is a pleasure to welcome the contributions of this new book to this important field. Whilst the existence of a substantial French research effort in the area has been well known, the scale and extent of the effort comes as something of a surprise. The rea.